Smart Learning in Elementary School: Professional Ethics of Teachers in the Era of Artificial Intelligence - Heru Siddik Nugroho (Global Education Journal, 2026)
Indonesia has gradually experienced growth in recent years, as reported by Katadata.co.id, where device usage reached 5.63 hours per day in 2020 and increased to 6.05 hours per day in 2023. His study aimed to examine the relationship between self-control and Cyberbullying behavior among university students in Aceh. A quantitative correlational design was employed. The participants consisted of 136 active university students aged 17–25 years. Data were collected using the Self-Control Scale and the Cyberbullying Scale, which had been adapted into Indonesian. Data analysis was conducted using Pearson Product Moment correlation after normality and linearity assumptions were met. The results indicated that there was no significant relationship between self-control and Cyberbullying behavior among students (r = −0.107; p = 0.214; p > 0.05). Most participants demonstrated moderate levels of self-control and low levels of Cyberbullying involvement. These findings suggest that self-control is not a predictor of Cyberbullying behavior among university students in Aceh. The results imply that Cyberbullying behavior in emerging adulthood may be more strongly influenced by other factors, such as social context, group norms, and cultural values. This study provides important implications for future research to explore broader psychosocial variables related to Cyberbullying in higher education settings.